Effect of Vitamin D Injection in Recurrent Benign Paroxysmal Positional Vertigo with Vitamin D Deficiency - Rhim, Gu Il (International Archives of Otorhinolaryngology, 2020)
Introduction There have been reports indicating that patients with frequently recurring benign paroxysmal positional vertigo (BPPV) had vitamin D deficiency, and some studies indicated that the treatment of severe vitamin D deficiency is effective in the reduction of the recurrence of BPPV.Objective The purpose of the present study was to examine the effects of Vitamin D3 injection on recurrence among patients with a 10 ng/mL or lower 25-hydroxyvitamin D blood concentration diagnosed with BPPV.Methods Among 99 patients with idiopathic BPPV with vitamin D deficiency, 25 patients (case group) were submitted to 3 to 4 injections of 200,000 IU of vitamin D3 in the first year. In total, 50 patients in the control group were selected through frequency matching, with 25 patients in the case group. Age, gender, and type of BPPV are used in matching variables with 1:2 matched data. The subjects of the study group were followed up for 24 months.Results The differences in relapse rates between the case and the control groups were examined using the non-parametric Kruskal-Wallis test for k independent samples. With regard to the relapse rates of the entire case and control groups by period, from 0 to 6 months (p < 0.531), from 7 to 12 months (p < 1.000), and from 13 to 24 months (p < 0.711), and in the entire study period (p < 0.883) there were no statistically significant differences.Conclusion The present case-control study indicated that vitamin D3 injection had no significant effect on the recurrence of BPPV patients with vitamin D deficiency when age, gender, and type of BPPV were homogeneous between the two groups.
Keywords: benign paroxysmal positional vertigo; vitamin D deficiency; recurrence